DAMPAK TOUR DE SINGKARAK TERHADAP EKONOMI PARIWISATA DI INDONESIA (STUDI KASUS: PROVINSI SUMATRA BARAT) - Aida Rahma Suci; Indra Pahlawan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research to analyze about the effect of event Tour de Singkarak towards economic tourism in Indonesia with study case in West Sumatera. Tour de Singkarak is one of classified MICE (meeting, incentive, convention, and exhibition) activity programs and yearly program by The Ministry of Tourism and Creative Economy Indonesian cooperation with Ministry of Province and Ministry of Regency in West Sumatera.This Research using library research. Source the data for this research obtained from Journals, books, essay, documents or report from the internet. The perspective used in this research is liberalism with globalization theory and tourism concept.This research to analyze about effect tourism promotion through international events towards economic region in field tourism.The tourism promotion doing by Tour de Singkarak activity since 2009 until 2014. Tour de Singkarak has been held six times and had a positive impact towards tourism sector in West Sumatera asan increase in trafficof foreigntourists, accommodationandlocal revenues.Keywords: MICE, Tour de Singkarak, Tourism Concept, Promotion Tourism, Local Revenues